New Premises and New Tools for Medical Care and Medical Education - Weed, L. L. (Methods of Information in Medicine, 1989)
Medical care and medical education can be supported more than in the past by using new tools and new premises for the effective linkage between bodies of knowledge and the use of that knowledge. The medical record can be converted from a source-oriented record to a problem-oriented record, enabling to trace not only what was done, but why it was done. These possiblities reveal new insights in the use of databases, problem lists, problem-oriented plans, and problem-oriented progress notes and flowsheets. It brings about a neW behavior in teaching which replaces memorizing facts, new possibilities for medical care, and new responsibilities both for physicians and patients. We now have knowledge-coupling tools that can be used directly with the patients at the time of problem solving. Patients are becoming active participants in this process, bringing about new roles for experts as well as expert systems.
Keywords: Problem-Oriented Medical Record; Medical Education; Medical Knowledge